Використання алгоритму хвильового трасування в задачах захисту інформації - Варава, М. С. (ХНУРЕ, 2022)
This work highlights the problem of the complexity of the projection of protection systems due to the rapid development of technology. Here is presented one of the ways to solve the problem of physical protection – the wave tracing algorithm. The method is based on finding the shortest path on the graph. The implementation consists of three points: initialization, wave propagation and path restoring. When processing a large amount of data. The execution of the algorithm takes a lot of time and money but allows to get a guaranteed result. It is also quite simple to implement.
Keywords: алгоритм хвильового трасування; захист інформації